IMPLEMENTASI E-GOVERNMENT DI DINAS KOMUNIKASI DAN INFORMATIKA (STUDI KASUS APLIKASI TANGERANG LIVE) - Oktafrianti, Devi; Aditya, Toddy; Nurhakim, Nurhakim (Kementerian Komunikasi dan Informatika R.I., 2020)
The Tangerang Live application is a communication hub in helping the government achieve organizational goals and communicate with the community. With the existence of e-government can provide public services more effectively and efficiently. In its implementation, there is a need for a combination of institutions, humans and technology. This research focuses on institutional factors in managing the Tangerang Live application and aims to be able to see the capabilities of the city of Tangerang and make it easier for the public to obtain information. This research method uses descriptive qualitative. The data were processed from the results of interviews and observations and then analyzed. The results show that there are several things that are of concern, such as human resources who are not yet competent, services handling is yet optimal and there is no standard operating procedure (SOP) related to the application used. The application is not as expected, it has been socialized but it depends on the level of awareness of the community.